2018
DOI: 10.1002/jctb.5649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extremely low bulk liquid DO on autotrophic nitrogen removal performance and NOB suppression in side‐ and mainstream one‐stage PNA

Abstract: BACKGROUND Results in the literature are divergent regarding dissolved oxygen (DO) level to ensure nitrite‐oxidizing bacteria (NOB) suppression in mainstream conditions. In this study, a one‐stage granular partial‐nitritation (PNA) was operated controlling the oxygen transfer over ammonium loading rate (OTR/ALR). The effects of extremely low DO availability on autotrophic nitrogen removal (ANR) performance and NOB suppression were assessed. RESULTS The strategy applied in the sequencing batch reactor (SBR) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The nitrite half-saturation coefficient (KS) of pure cultures of Nitrobacter was 0.69-7.6 mg-N l -1 , while pure cultures of Nitrospira showed lower values of 0.13-0.38 mg-N l -1 [31]. The oxygen half-saturation coefficient (KO) of mixed cultures of Nitrobacter was 0.43-5.31 mg l -1 [3,33,34] while the value of KO of Nitrospira was 0.33-0.54 mg l -1 [33,35]. The difference of KS and KO between Nitrobacter and Nitrospira allows them to be dominant in distinct environments.…”
Section: Nob Community Structurementioning
confidence: 97%
See 1 more Smart Citation
“…The nitrite half-saturation coefficient (KS) of pure cultures of Nitrobacter was 0.69-7.6 mg-N l -1 , while pure cultures of Nitrospira showed lower values of 0.13-0.38 mg-N l -1 [31]. The oxygen half-saturation coefficient (KO) of mixed cultures of Nitrobacter was 0.43-5.31 mg l -1 [3,33,34] while the value of KO of Nitrospira was 0.33-0.54 mg l -1 [33,35]. The difference of KS and KO between Nitrobacter and Nitrospira allows them to be dominant in distinct environments.…”
Section: Nob Community Structurementioning
confidence: 97%
“…The process can be promoted by providing environmental conditions that suppress the activity of nitrite-oxidizing bacteria (NOB) while allowing the activity of ammonia-oxidizing bacteria (AOB) to occur. Such conditions include maintaining high pH [1], high temperature (>35°C) [2], and/or low oxygen (0.3-0.5 mg l -1 ) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Nitrospira spp. are usually the dominant NOB in domestic wastewater treatment by partial nitritation-anammox, 8 but recently it is known that they also include complete ammonia-oxidizing bacteria (CAOB). 9,10 In fact, the partial nitritation-anammox process can even be overtaken by CAOB, turning into a complete nitrification reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, anammox-based wastewater nitrogen removal process that combines partial-nitritation with anammox in granular sludge reactors, biofilm reactors, and filters have been scaled up from lab-scale to pilot- and full-scale. However, domestic wastewater treatment by partial nitritation-anammox is often challenged by the overgrowth of nitrite oxidizing bacteria (NOB). , Nitrospira spp. are usually the dominant NOB in domestic wastewater treatment by partial nitritation-anammox, but recently it is known that they also include complete ammonia-oxidizing bacteria (CAOB). , In fact, the partial nitritation-anammox process can even be overtaken by CAOB, turning into a complete nitrification reactor . However, roles of CAOB in the anammox-based wastewater nitrogen removal process remained unclear, and exploring the relationship between CAOB and AnAOB is of great importance for achieving efficient nitrogen removal.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Wang (2013) and Wett et al (2013) reported higher 𝐾 𝑂 2 value for AOB when reactors were kept at lower temperature for the long-term. Reports from Li et al (2019a), del Rio et al (2019 and Akaboci et al (2018b) suggested that low DO needed to be supplemented with other strategies to achieve better NOB suppression in mainstream condition. Floating oxygen availability control strategy relies on online monitoring of ammonium, nitrate, or pH to regulate aeration.…”
Section: Fixed Oxygen Availability Setpoint Strategymentioning
confidence: 99%